Process induced degradation of carbamazepine during hot melt extrusion - Sarbamangala Bose; Anant Paradkar; Adrian Kelly; Harika Magam (University of Huddersfield Press, 2023)
The aim of this study was to evaluate hot melt extrudates of carbamazepine (CBZ) for presence of process induced degradation product iminostilbene (IMB) and quantifying using high performance liquid chromatography (HPLC). CBZ was used as model drug. Hot-melt extrusion (HME) was performed to prepare solid dispersions. Different grades of compatible polymers were used. Drug loading, processing temperature and screw rotations per minute (RPM) showed significant effect on degradation of CBZ The extrudates were characterized by differential scanning calorimetry (DSC), X-ray diffraction (XRD), Fourier transform infrared (FTIR) studies. DSC and XRD data confirmed formation of amorphous solid dispersions of CBZ. HPLC was performed to quantify percentage amount of CBZ and IMB. Process induced degradation was significantly varied depending on polymer grade and (w/w) percentage combinations. In addition, processing temperature and RPM had direct effect on percentage of IMB formation.